因式分解(1)4(x+y)²-25(2)4a²-(a²+1)²(3)x²+xy-3x-3y

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/17 03:24:57

因式分解(1)4(x+y)²-25(2)4a²-(a²+1)²(3)x²+xy-3x-3y
因式分解(1)4(x+y)²-25(2)4a²-(a²+1)²(3)x²+xy-3x-3y

因式分解(1)4(x+y)²-25(2)4a²-(a²+1)²(3)x²+xy-3x-3y
(1)4(x+y)²-25
=(2x+2y+5)(2x+2y-5)
(2)4a²-(a²+1)²
=(2a+a²+1)(2a-a²-1)
=-(a+1)²(a-1)²
(3)x²+xy-3x-3y
=x(x+y)-3(x+y)
=(x-3)(x+y)

解;①原式=(2x+2y)¹-5²
=(2x+2y-5)(2x+2y+5)
②原式=(2a)²-(a²+1)²
=(2a-a²1)(2a+a²+1)
=-(a-1)²(a+1)²
③原式=x²-3x+xy-3y
=x(x-3)+y(x-3)
=(x+y)(x-3)

(1)用公式a²-b²=(a+b)(a-b)分解;(2)先去括号、合并,再用公式a²-2a+1=(a-1)²;(3)用提取公因式的方法分解
(1)(2x+2y+5)(2x+2y-5)
(2) - (a²-1)²
(3) (x-3)(x+y)